Modeling and optimization of hybrid microgrid energy system: a case study of University of Abuja, Nigeria - Timothy Oluwaseun Araoye; Evans Chinemezu Ashigwuike; Sadiq Abubakar Umar; Taiwo Felix Adebayo; Sochima Vincent Egoigwe; Matthew Chinedu Odo; Chikammadu Emmanuel Opata; Ohagwu Walte Akachukwu (Institute of Advanced Engineering and Science, 2023)
This research work modelled and optimized the hybrid microgrid energy system for electricity generation at the University of Abuja, Nigeria, using PV, wind, diesel, and battery renewable energy resources. The model and optimization of the system are performed through HOMER software. The estimated university average annual power consumption is 2355 kWh/day, and the optimal load demand is 313.40 kWp. The PV/wind/diesel/ converter/battery hybrid system has the lowest cost of energy (COE) of 0.1616 /kWh, operating cost of 50,592, and net present cost (NPC) of 1,795,026 but diesel/wind/converter/battery hybrid system has highest COE of 0.4242 /kWh and NPC of 4,710,983. The optimal total electricity generated is 1,272,778 kWh/yr while electricity generated by PV contribute the highest energy of 1,030,485 kWh/yr (81%), whereas diesel generator and wind produced energy of 93,927 kWh/yr (7.38%) and 148,366 kWh/yr (11.7%) respectively. The wind/diesel/converter/battery hybrid system produced carbon dioxide (CO2) of 557,749 kg/yr. The most environmentally friendly is the wind/PV/battery and PV/battery hybrid system without pollutants emissions, but the diesel/wind/battery hybrid system has the highest rate of pollutants emissions. The result shows that PV’s electrical power is extremely high from February to June, which causes a high rate of irradiance within the specified period.